Prakiraan Kecepatan Angin Menggunakan Metode Triple Exponential Smoothing di Pantai Pangandaran - Dimara Kusuma Hakim; Yuana Wangsa Putri Setiawan; Supriyono; Maulida Ayu Fitriani4 (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Indonesia as a maritime country with a long coastline, holds significant potential in the marine and tourism sectors. However, these sectors are often disrupted by adverse weather conditions, particularly irregular wind speeds. Accurate wind speed forecasting is therefore essential for disaster mitigation. This study aims to forecast wind speed at Pantai Pangandaran using the Triple Exponential Smoothing (TES) method, which is more effective in handling data fluctuations with trend and seasonal patterns. The data used includes daily data from January 2014 to September 2024. The results show that the TES method provides highly accurate forecasts, with a low error rate evaluated through an RMSE of 0.51 and a MAPE of 17.85% for wind speed. These forecasts are expected to support disaster mitigation, enhance safety, and improve the efficiency of activities in coastal areas, particularly at Pantai Pangandaran, in facing adverse weather conditions.